Evaluation of DMSO-free cryopreservation reagent XT-Thrive for establishment of mesenchymal stem cell bank platform - Lam, Alan Tin-Lun; Shridhar, Arthi; Handral, Harish K.; Lee, Jialing; Oh, Steve; Wei, Xiaoxi (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionEffective cryopreservation is essential for the clinical application and large-scale banking of mesenchymal stem cells (MSCs). This study compares the performance of a novel DMSO-free cryoprotectant, XT-Thrive®, with a conventional DMSO-based solution, CryoStor® CS10, in preserving both commercial and donor-derived bone marrow MSCs (BM-MSCs). Evaluations focused on viability, recovery, proliferation, and functional characteristics across master cell bank (MCB), working cell bank (WCB), and final product (FP) stages.MethodsIn Part 1, commercial BM-MSCs were cryopreserved in XT-Thrive or CS10 and evaluated for pre-freeze viability, post-thaw survival (up to 6 h), and recovery in 2D and 3D cultures. In Part 2, donor-derived BM-MSCs were cryopreserved at passages 2 (MCB), 4 (WCB), and 8 (FP), and assessed for cumulative population doubling levels (cPDL), immunophenotype, clonogenicity, differentiation potential, secretome profile, telomere length, karyotype stability, and tumorigenicity.ResultsXT-Thrive–preserved MSCs maintained >90% pre-freeze viability after 24-h room temperature holding, compared to a ∼40% drop with CS10. Post-thaw viability at 6 h remained above 85% with XT-Thrive, vs. 60%–70% with CS10. In 3D microcarrier cultures under serum-free conditions, XT-Thrive-preserved MSCs demonstrated a ∼2.5-fold improvement in viable cell recovery compared to CS10, which failed to support recovery and expansion. XT-Thrive–preserved donor MSCs showed significantly higher cPDL at passages 8 FP (19.8 ± 0.4 vs. 15.4 ± 0.5, p < 0.001). CFU-F efficiency was also higher (∼23% vs. ∼15%). Furthermore, XT-Thrive–preserved MSCs exhibited enhanced osteogenic differentiation and increased secretion of FGF2 and HGF (1.8-fold and 2.1-fold increase, respectively), without compromising karyotype integrity, telomere length, or safety in vivo.ConclusionXT-Thrive provides superior pre-freeze stability, post-thaw recovery, expansion potential, and osteogenic functionality compared to CS10, while maintaining MSC identity and genomic stability. These results support XT-Thrive as a promising DMSO-free alternative for clinical-grade MSC biobanking and manufacturing.